Role of electrolyte concentrations and renin‐angiotensin‐aldosterone activation in the staging of canine heart disease. (26th November 2019) - Adin, Darcy; Kurtz, Kari; Atkins, Clarke; Papich, Mark G.; Vaden, Shelly
Abstract: Background: Refractory congestive heart failure (CHF) and associated diuretic resistance are not well defined. Objectives: To characterize renal function, electrolyte concentrations, indices of diuretic efficacy, and renin‐angiotensin‐aldosterone system (RAAS) activation in dogs with naturally occurring heart disease (HD) in American College of Veterinary Internal Medicine stages B1, B2, C, and D and to determine their usefulness in defining HD stages. Animals: Group 1:149 dogs with HD stages B1, B2, C, and D. Group 2:22 dogs with HD stages C and D. Methods: Group 1: Renal parameters, serum and urine electrolyte and diuretic concentrations, and urine aldosterone concentrations were measured. Medication dosages and measured variables were compared among stages. Correlation of furosemide dosages to serum concentrations was explored. Group 2: Angiotensin‐converting enzyme activity and RAAS components were measured and compared among CHF stages. Results: Serum chloride concentration was the best differentiator of HD stage. Furosemide PO dosages (≤6 mg/kg/day) were weakly correlated with serum furosemide concentrations, whereas higher dosages were not significantly correlated. Angiotensin‐converting enzyme inhibitor dosage and RAAS inhibition were greater in stage D, compared to stage C dogs. Conclusions and Clinical Importance: Hypochloremia is a useful marker for stage D HD in dogs. Poor furosemide dosage correlation to serum concentration may indicate variable and poor absorption, especially at higher dosages, advanced disease, or both. A small number of stage D dogs met proposed criteria for diuretic resistance. Greater RAAS inhibition in stage D versus stage C indicates effectiveness of RAAS‐suppressive treatments in this group of dogs with refractory CHF.